2014
DOI: 10.1111/ppl.12148
|View full text |Cite
|
Sign up to set email alerts
|

The 9-lipoxygenase Osr9-LOX1 interacts with the 13-lipoxygenase-mediated pathway to regulate resistance to chewing and piercing-sucking herbivores in rice

Abstract: Oxylipins produced by the 13-lipoxygenase (LOX) have been reported to play an important role in plant defense responses to herbivores. Yet, the role of oxylipins produced by the 9-LOX pathway in this process remains largely unknown. Here we cloned a gene encoding a chloroplast-localized 9-LOX, Osr9-LOX1, from rice. Transcriptional analysis revealed that herbivore infestation, mechanical wounding and jasmonic acid (JA) treatment either repressed or did not enhance the level of Osr9-LOX1 transcripts at early sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 39 publications
2
52
0
Order By: Relevance
“…To understand how ECO 2 affect W + OS‐induced JA and JA‐Ile, the expression levels of important genes involved in JA and JA‐Ile biosynthesis in tobacco and rice were determined. LOX ( lipoxygenase ) (Halitschke and Baldwin ; Zhou et al ) , AOS ( Allene oxide synthas e) (Halitschke et al ), AO C ( allene oxide cyclase ) (Stenzel et al ), OPR ( 12‐oxophytodienodate reductase ) (Tani et al ; Koo et al ), and JAR ( jasmonate‐resistant ) (Kang et al ; Fukumoto et al ) were selected and quantified by q‐PCR (Wasternack and Song ). In tobacco, W + S. litura OS‐induced NtLOX (1.5 h), NtAOC (0.5 h), and NtJAR (1.5 h), were 54%, 95%, and 37% elevated, respectively, under ECO 2 (Figure A, C, E), and the expression levels of NtAOS and NtOPR did not alter (Figure B, D).…”
Section: Resultsmentioning
confidence: 99%
“…To understand how ECO 2 affect W + OS‐induced JA and JA‐Ile, the expression levels of important genes involved in JA and JA‐Ile biosynthesis in tobacco and rice were determined. LOX ( lipoxygenase ) (Halitschke and Baldwin ; Zhou et al ) , AOS ( Allene oxide synthas e) (Halitschke et al ), AO C ( allene oxide cyclase ) (Stenzel et al ), OPR ( 12‐oxophytodienodate reductase ) (Tani et al ; Koo et al ), and JAR ( jasmonate‐resistant ) (Kang et al ; Fukumoto et al ) were selected and quantified by q‐PCR (Wasternack and Song ). In tobacco, W + S. litura OS‐induced NtLOX (1.5 h), NtAOC (0.5 h), and NtJAR (1.5 h), were 54%, 95%, and 37% elevated, respectively, under ECO 2 (Figure A, C, E), and the expression levels of NtAOS and NtOPR did not alter (Figure B, D).…”
Section: Resultsmentioning
confidence: 99%
“…The increased substrate utilization of linolenic acid by ZmLOX3 may be a consequence of its subcellular localization. Recently, it has been reported that the rice orthologue of ZmLOX3 is plastid‐localized (Zhou et al ., ), the membranes of which are rich in linolenic acid. These results suggest that LOX3‐derived oxylipins, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Con, Control plants. (Zhou et al, 2014) and OsNPR1 , have been described. In other plants, SA signaling and jasmonate catabolism have been shown to be involved in attenuating herbivore defenses (Pieterse and Van Loon, 2004;Campos et al, 2014).…”
Section: Oswrky53 Functions As a Negative Feedback Modulator Of Mpk3/mentioning
confidence: 99%